Combining a Mutant Allele of FAD2-1A with HD Improves the ω-6/ω-3 Ratio in Soybeans - Hwayeop Kim; Hyun Jo; Jeong-Dong Lee (Agronomy, 2023)
The intake of foods with unbalanced ω-6/ω-3 ratios causes various health problems. Commodity soybeans generally have a ω-6/ω-3 ratio of 6–7:1. The recommended ratio in terms of health benefits is <4:1. This study aimed to identify the appropriate combination of mutant alleles that can reduce the ω-6/ω-3 ratio using three segregating soybean populations. F2 individuals from each population were genotyped for three different alleles of microsomal delta-12 fatty acid desaturase 2 enzyme (FAD2-1A) and an allele of homeodomain-like transcriptional regulator (HD) genes, and their five major fatty acids were assessed. F2 seeds carrying both fad2-1a and hd had slightly different ω-6/ω-3 ratios according to the different fad2-1a alleles. The fad2-1aDEL, fad2-1aS117N, and fad2-1aW293STOP alleles combined with a hd allele resulted in ω-6/ω-3 ratios with a range of 1.9–2.7:1, 2.7–3.9:1, and 2.6–3.6:1 in soybean seeds, respectively. This study revealed that the induction of mutations in FAD2-1ADEL and HD was the most efficient strategy to improve the ω-6/ω-3 ratio and elevate the ω-3 fatty acid concentrations in soybean seeds. These results provide useful information in soybean breeding programs to release a new soybean cultivar with a lower ω-6/ω-3 ratio and elevated ω-3 fatty acids, which can be a beneficial ingredient for soybean-based foods.